1999
DOI: 10.1007/s004649901080
|View full text |Cite
|
Sign up to set email alerts
|

Hazards of laparoscopic adrenalectomy for Conn's adenoma

Abstract: A 74-year-old man with primary aldosteronism had a small tumor (27 x 23 mm) of his right adrenal gland successfully removed by a transperitoneal laparoscopy. Despite absence of malignancy in the resected tumor and complete relief of all symptoms in the immediate postoperative period, recurrence occurred 6 months later. The tumor behaved as a carcinoma spread in the peritoneal cavity, and the patient eventually died with peritoneal carcinomatosis. We suggest that the laparoscopic technique coupled with pneumope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 10 publications
0
37
0
4
Order By: Relevance
“…They however did not compare open surgery to laparoscopic surgery, and only included four ACC patients among whom one needed a conversion to an open procedure and one developed a pelvic 18-cm recurrence 6 months after initial surgery that was compatible with PC. Of note, clinical cases of PC occurring in ACC patients after LA were recently reported (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…They however did not compare open surgery to laparoscopic surgery, and only included four ACC patients among whom one needed a conversion to an open procedure and one developed a pelvic 18-cm recurrence 6 months after initial surgery that was compatible with PC. Of note, clinical cases of PC occurring in ACC patients after LA were recently reported (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…A second laparotomy was undertaken to excise all tumor deposits and to install intraperitoneal chemotherapy, which was followed by intravenous chemotherapy. Foxius et al 16 observed peritoneal carcinomatosis 6 months after laparoscopic removal of a right 2.7-cm aldosterone-producing adrenal lesion. Despite splenectomy and omentectomy followed by mitotane chemotherapy, the patient died 20 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, three other cases of recurrence of adrenal cancer after laparoscopic adrenalectomy have been reported. [15][16][17] Hamoir et al 15 described a patient with a 12-cm androgenproducing right adrenal tumor that had been removed through a subcostal laparotomy after 4 hours of troublesome laparoscopic dissection. Diffuse peritoneal adrenal cancer was found at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data from the literature confirm that laparoscopic adrenalectomy is safe and effective for malignant adrenal tumors. In some studies, outcome results with regard to peritoneal carcinomatosis, positive resection margins, and time to recurrence showed no statistically significant differences between open and laparoscopic approaches [12,[28][29][30][31][32][33]. In other studies with regard to ACC, oncologic outcomes of laparoscopic adrenalectomy were not comparable to open adrenalectomy [17,34,35].…”
Section: Indication For Adrenalectomymentioning
confidence: 95%